2020
DOI: 10.20945/2359-3997000000260
|View full text |Cite
|
Sign up to set email alerts
|

Impact of schooling in the HIV/AIDS prevalence among Brazilian transgender women

Abstract: Objective: Discrimination and bullying are common conditions among LGBT people. During schooling, these practices compromising education. The aim of this study is to evaluate educational attainment among Brazilian transgender women (TW) and how their education level affects the risk of HIV infection. Study design: a cross-sectional population-based study. Subjects and methods: 95 adult TW were selected. Information concerning verbal and physical aggression, school dropout, school years (SY), and educational le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
7
0
2
Order By: Relevance
“…[19] In addition, the lack of preparation of Primary Health Care to provide quality and humanized care was another point raised by the study. [19] Education is also an in factor fluency, according to data from Batista and collaborators [2020], [20] who demonstrated an average number of school years for HIVpositive trans women up to 2.9 years lower than the same group with negative serology, in a context where transsexuals as a whole already have a high school dropout rate, resulting in fewer years of study.…”
Section: Resultsmentioning
confidence: 99%
“…[19] In addition, the lack of preparation of Primary Health Care to provide quality and humanized care was another point raised by the study. [19] Education is also an in factor fluency, according to data from Batista and collaborators [2020], [20] who demonstrated an average number of school years for HIVpositive trans women up to 2.9 years lower than the same group with negative serology, in a context where transsexuals as a whole already have a high school dropout rate, resulting in fewer years of study.…”
Section: Resultsmentioning
confidence: 99%
“…There are free public universities; however, they are highly competitive, and a spot is not guaranteed. The study by Batista et al, 4 which found an association between HIV prevalence and lower level of education level, also noted that Brazilian transgender women who experienced physical aggression in school attended school for 4 years fewer than those who did not have such experiences. Low education may be a driver for engaging in sex work among transgender women who face fewer educational and economic opportunities.…”
mentioning
confidence: 90%
“…2 Another study inversely associated level of education with higher prevalence of HIV among transgender women in Brazil. 4 These findings suggest the importance of social determinants on HIV acquisition among transgender women, although HIV incidence was not directly measured. Directly observed measures of HIV incidence in longitudinal studies among transgender women are rare worldwide, 5 yet needed to determine the current trajectory of the HIV epidemic, identify causal risk factors of acquiring infection, and prioritize prevention programs such as pre-exposure prophylaxis (PrEP).…”
mentioning
confidence: 96%
“…For example, trans women may avoid healthcare settings and HIV testing due to anticipated provider stigma based on prior discriminatory behavior [14]. Structural barriers that reduce access to education may lead to lower HIV knowledge and risk perception, presenting barriers to HIV testing [15,16]. Furthermore, trans women face intersectional discrimination from the interaction between HIV stigma and anti-trans stigma, which together foster unique experiences of oppression that present additional structural barriers to HIV testing [17].…”
Section: Introductionmentioning
confidence: 99%